Feeding ecology of the Greenland shark under different ice conditions ... - Fisk, Aaron; McMeans, Bailey; Fryer, Brian; Idrobo, Carlos; Berkes, Fikret; Arts, Michael; Campana, Steven; Dennard, Susan (Borealis, 2012)
To date, five sampling trips to Cumberland Sound have been completed, three during times of open water (July-August 2007, 2008, 2009) and two during times of ice cover (April 2008, 2009). Preliminary results indicate that the Greenland shark is feeding at a high trophic position and on benthic and pelagic resources, based on chemical tracers. The Greenland shark appears to feed on seal during both open water and ice cover, and does not appear to target different resources with season based on chemical tracers. However, some consumers, like ringed seals and predatory zooplankton appear to switch to a lower trophic level during open water, likely to exploit large number of Calanus copepods. Results from several satellite tags suggest that sharks are highly mobile, with regards to depth (i.e. vertical movement) and distance (i.e. horizontal movement). Based on our hierarchical models regarding turbot, we found a strong connection between environmental fluctuations and variations in fishery catch rates between ... : Type: Research Program: Notes: IPY-Greenland Shark This metadata record corresponds to an IPY project. Studies completed under this research project are identified as related materials. These studies can also be retrieved using the Polar Data Catalogue.; ...